Seaweed, enteromorpha intestinalis, as a diet for nile tilapia oreochromis niloticus fry - Siddik, Muhammad Abu Bakar; Rahman, Mohammad Mustafizur; Nguyen, Thi Ngoc Anh; Nevejan, Nancy; Bossier, Peter (Taylor & Francis Group, 2015)
A 42-d feeding trial was carried out to assess the potential use of the seaweed Enteromorpha intestinalis (“gutweed”) as a food source for monosex Nile tilapia (Oreochromis niloticus) fry and to determine a maximum threshold fishmeal substitution rate. Six fish diets randomly assigned to tilapia juvenile and in triplicate were compared: replacing 0%, 10%, 20%, 30%, 40%, and 50% of fishmeal protein with a gutweed protein blend. Highest growth and cost reduction in tilapia fry production was observed in fish fed a 20% replacement diet.